The Writer's World : paragraph patterns and the essay - Gaetz, Lynne (Pearson Prentice Hall, 2006)
The Writer’s World addresses the diverse needs of students by meeting the needs of nonnative English speakers, visual learners and students with varying skill levels! Now, The Writer's World addresses the diverse needs of instructors! Prentice Hall is proud to offer The Writer’s World: Paragraphs and Essays in four individual volumes. Developed to provide maximum flexibility for both instructors and students, the volumes were created directly from the pages of The Writer’s World: Paragraphs and Essays by Lynne Gaetz and Suneeti Phadke. Volume two, The Writer's World: Paragraph Patterns and the Essay, gives students a solid overview of the patterns of development. It also covers the parts of the essay and explains how students can apply the nine patterns of development to essay writing. Volume two may be used as a stand alone item or in conjunction with any of the other volumes.